Effect of Hemodialysis On Plasma Osmolarity In Patients With Chronic Renal Failure - Al-Shamma, Yesar M.H.; Aziz, Abdul- Aziz A.; Al-Sunbly, Yihia Mousa; Al-Turjoman, Sadiq MAA. (Journal of the Faculty of Medicine Baghdad, 2008)
Back ground: The study was conducted on fifty patients (27 males and 20 females) with chronic renal failure (CRF) undergoing maintenance hemodialysis (HD), atartificial Kidney unit, Al- Hakeem Hospital / Najaf, during the perioed from April to June 2008.Patients & methods: Plasma osmolarity ( Posm), plasma creatinine (P cr ) plasma urea (P urea)>plasma sodium (P Na)and plasma potassium ( P k )were measured forall patients before and after dialysis.Results: The paired t -test was used to compare the pre-dialysis values with the post dialysis values and simple linear correlation to study the relation between (PNa), and ( Posm), p values less than 0.05 considered not significant. The result of study showed a significant decrease in the means of P Na , P k, P cr, P urea and Posmafter dialysis in comparison with the pre-dialysis values ( p